2009
DOI: 10.1007/s00441-009-0883-x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, characterization and osteogenic differentiation of adipose-derived stem cells: from small to large animal models

Abstract: One of the most important issues in orthopaedic surgery is the loss of bone resulting from trauma, infections, tumours or congenital deficiency. In view of the hypothetical future application of mesenchymal stem cells isolated from human adipose tissue in regenerative medicine, we have analysed and characterized adipose-derived stem cells (ASCs) isolated from adipose tissue of rat, rabbit and pig. We have compared their in vitro osteogenic differentiation abilities for exploitation in the repair of critical os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
82
0
5

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(108 citation statements)
references
References 41 publications
(57 reference statements)
21
82
0
5
Order By: Relevance
“…In this study, we isolated human MSCs from adipose tissue and bone marrow of the same donors to compare the morphology, proliferation ability, surface antigens and cardiomyogenic differentiation capacity of the two populations. Consistent with other studies (17,18), no difference in morphology was observed between ASCs and BMSCs. Prior to treatment with 5-azacytidine, both ASCs and BMSCs stained positively for CD29, CD44 and CD105, although negatively for CD34 and CD45; however, the difference in surface marker expression appears to be with CD49d and CD106.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, we isolated human MSCs from adipose tissue and bone marrow of the same donors to compare the morphology, proliferation ability, surface antigens and cardiomyogenic differentiation capacity of the two populations. Consistent with other studies (17,18), no difference in morphology was observed between ASCs and BMSCs. Prior to treatment with 5-azacytidine, both ASCs and BMSCs stained positively for CD29, CD44 and CD105, although negatively for CD34 and CD45; however, the difference in surface marker expression appears to be with CD49d and CD106.…”
Section: Discussionsupporting
confidence: 92%
“…On the ultrastructural level, they display normal morphology of the protheosynthetically active cells. Similar observations from experiments with somatic stem cells originated from various tissues were recorded by our group and other authors, not only in human but also in other species [7], [8], [10]- [12].…”
Section: Discussionsupporting
confidence: 76%
“…The isolation and culture of rASCs were performed, as previously described. 18,19 After rinsing in 0.25% chloromycetin and phosphate-buffered saline (PBS), the fresh adipose tissues were cut into small pieces and then treated with 0.10% collagenase I (Worthington Biochemical Corp.) under shaking at 37°C for 60 min. After digestion, the collagenase I was neutralized with low-glucose Dulbecco's modified Eagle's medium (LG-DMEM; Gibco) supplemented with 10% fetal bovine serum (FBS; Gibco), and the suspension was filtered through a 200-mm nylon mesh to remove the undigested tissue and then centrifuged at 1200 g for 10 min.…”
Section: Isolation and Culture Of Rascs In Vitromentioning
confidence: 99%